Comparative analysis of cold and hot water therapies on agility and power metrics in collegiate futsal athletes / Nur Fatin Syamimi Parikh ... [et al.]. - Parikh, Nur Fatin Syamimi; Mohamed, Muhamad Noor; Azreen, Noor Azila; Raja Hussein, Raja Nurul Jannat; Abu Kassim, Nurul Ain; Adnan, Muhamad Aizzat; Mazaulan, Mardiana (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the effects of cold-water therapy (CWT) and hot-water therapy (HWT) on muscle performance in UiTM Negeri Sembilan futsal players. By evaluating their influence on agility and power, the research seeks to clarify the long-term effects of CWT and HWT on muscle contractile properties, contributing to strategies for optimizing athletic performance [1]. This study used quasi - experimental design involved 10 male UiTM Negeri Sembilan futsal players aged 18–25 years, meeting strict eligibility criteria. Cold-water therapy (15°C, 15 min) [2] and hot-water therapy (38–40°C, 15 minutes) [3] were administered. Data were collected before treatment, immediately after treatment, and 72 hours post-treatment. Muscle performance was assessed using agility T-tests [4] and broad jump measurements [5]. Participants had no lower limb injuries in the past six months.